The Structure of Signs in Awaydays Film: A Semiotic Analysis by Ferdinand De Saussure's Theory (2009) - Febby Pratama; Wahyu Budi (INDO PUBLISHING, 2025)
This study investigates the structure of signs in the British film Awaydays (2009) using Ferdinand de Saussure’s semiotic theory. Saussure conceptualizes signs as a combination of the signifier (the physical form) and the signified (the conceptual meaning), which together produce meaning within a linguistic and cultural system. The research treats the film not merely as entertainment but as a cultural text embedded with symbolic messages. Through a descriptive qualitative method, the study identifies and interprets various signs present in visual and verbal elements, including costumes, music, facial expressions, locations, and dialogue. These signs are analyzed in relation to themes of identity, subculture, alienation, and personal transformation. Particular emphasis is placed on how the protagonist, Carty, and his interactions with “The Pack” represent internal struggles and external pressures within the context of 1970s English football hooliganism. The findings show that the film uses semiotic structures to explore issues of masculinity, belonging, and youth rebellion. It reflects how signs operate not only to build narrative coherence but also to reinforce or challenge dominant ideologies. This analysis highlights the capacity of cinema to function as a site of meaning-making through structured sign systems. By applying Saussure’s theoretical framework, the study demonstrates that semiotics can provide critical insight into the ways films communicate complex social and psychological themes.